Anxiofit‐1 and reduction of subthreshold and mild anxiety: evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006. (22nd October 2020) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: Following an application from Anxiofit Ltd., submitted for authorisation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of Hungary, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to Anxiofit‐1 and reduction of subthreshold and mild anxiety. The food, Anxiofit‐1, Echinacea angustifolia root extract, standardised for the content of echinacoside (at least 3%) and the profile of alkamides, which is the subject of the health claim, is sufficiently characterised. The Panel considers that reduction of subthreshold and mild anxiety is a beneficial physiological effect. Subthreshold and mild anxiety are risk factors for anxiety and depressive disorders. One human intervention study showed an effect of Anxiofit‐1 (80 mg/day given for 7 days) on the state anxiety and not on the trait subscale in subjects with subthreshold or mild anxiety. These results are supported by two human intervention studies conducted with Anxiofit‐1 at 40 mg/day for 7 days and 6 weeks, respectively, which, on their own, cannot be used for the substantiation of the claim either because of methodological limitations or because the results cannot be extrapolated to the target population for the claim. All the human intervention studies submitted have been conducted in a similar setting, the results of the study with Anxiofit‐1 given at 80 mg/day have not been confirmed by other research groups. The information submitted by the applicant does not provide evidence for a plausible mechanism by which Anxiofit‐1 could exert the claimed effect. The Panel concludes that the scientific evidence is insufficient to establish a cause and effect relationship between the consumption of Anxiofit‐1 and reduction of subthreshold and mild anxiety.